THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND TOTAL ASSET TURNOVER ON STOCK PRICES IN THE SECTOR INDUSTRIES REGISTERED ON BEI 2020-2021 PERIOD - Hidayati, Efian Rohmah; Albertus, Redy Herinanto; Natalia, Bonifasia Ekta Fima (Universitas Pembinaan Masyarakat Indonesia, 2023)
This study aims to determine the effect of the Current Ratio, Debt to Equity Ratio, and Total Assets Turn Over on stock prices in the industrial sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period, either partially or simultaneously. The population in this study is 56 industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021. The research sample is 10 companies obtained by purposive sampling technique. The method used in this research is a quantitative method. The data collection technique used is documentation. The analytical method used is multiple linear regression test. The results showed that partially the CR and DER variables had a positive and significant effect on stock prices, while TATO had a negative and insignificant effect. Simultaneously the variables CR, DER, and TATO have no significant effect on stock prices. The CR, DER, and TATO variables can explain the share price of the agricultural sector industry listed on the Indonesia Stock Exchange (IDX) in 2020-2021 of 5.1%. JEL Classification: M41, M42